Transparent, fracture-tough polymer resin for dental moldings
The existing dental materials are solved by using components such as ABA or AB block copolymers, urethane di(meth)acrylate remote claws and block copolymers in dental materials, combined with photoinitiators and fillers. Inadequate transparency, fracture toughness and mechanical properties in additive manufacturing have achieved efficient preparation of dental materials.
Patent Information
- Application Number
- CN202210373034.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-07
- Filing Date
- 2022-04-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-04-11
AI Technical Summary
It is difficult for existing dental polymer materials to meet high transparency, good fracture toughness and mechanical properties at the same time in additive manufacturing, and have high polymer shrinkage and high material brittleness, which affects dimensional stability and aesthetics.
Free radical polymerizable dental materials using ABA or AB block copolymers, preferably aromatic or bicyclic/tricyclic mono(meth)acrylate, urethane di(meth)acrylate and truncated The segment copolymer, combined with an appropriate amount of photoinitiator and filler, adjusts the crosslinking density to improve fracture toughness and transparency.
Materials with high fracture toughness and work-of-break in water are achieved while maintaining good bending strength and transparency, reducing the viscosity and inherent color of the polymer, suitable for additive manufacturing of dental molded bodies.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The invention relates to free-radically polymerizable compositions which are particularly suitable as dental materials for the production of dental moldings, such as artificial teeth, dental prostheses, inlays, onlays, splints (occlusal splints), crowns, bridges, veneers and orthodontic appliances by additive processes. Background Art
[0002] Conventional dental polymerization systems are mainly composed of a mixture of transparent liquid monomers, initiator components, stabilizers and pigments (J. Viohl, K. Dermann, D. Quast, S. Venz, Die Chemie Füllungskunststoffe, Carl Hanser Verlag, Munich-Vienna 1986, 21-27). Mixtures of dimethacrylates are used primarily as monomers for building polymer networks, for example in filling materials (see A. Peutzfeldt, Resin composites in dentistry: The monomer systems, Eur. J. Oral. Sci. 105 (1997) 97-116; N. Moszner, T. Hirt, New Polymer-Chemical Developments in Clinical Dental Polymer Materials: Enamel-Dentin Adhesives and Restorative Composites, J. Polym. Sci. Part A: Polym. Chem. 50 (2012) 4369-4402). Examples of these are the high viscosity dimethacrylates 2,2-bis[4-(2-hydroxy-3-methacryloxypropyl)phenyl]propane (bis-GMA) and 1,6-bis-[2-methacryloxyethoxycarbonylamino]-2,4,4-trimethylhexane (UDMA) used as diluent monomers and the low viscosity dimethacrylates bismethacryloxymethyltricyclo[5.2.1.]decane (TCDMA), decanediol-1,10-dimethacrylate (D3MA) and triethylene glycol dimethacrylate (TEGDMA). In contrast, the monofunctional monomer methyl methacrylate (MMA) is mainly used in dental prostheses and, despite its low viscosity, is very volatile.
[0003] Depending on the field of use, further additives and initiators suitable for initiating free radical polymerization are added. Photoinitiators in the visible range are used to initiate polymerization using light, which form free radicals with blue light and are characterized by a good curing depth and very good whitening properties. Prosthetic materials contain as an essential component powdered polymethyl methacrylate (PMMA), which forms a paste with MMA. Curing takes place thermally or with redox initiators. In the case of filling composites and sealing binders, a high proportion of inorganic fillers provides high flexural strength and surface hardness, where, however, the fillers can have an adverse effect on transparency.
[0004] The main problem of free radical methacrylate polymers is polymerization shrinkage (ΔV P ), i.e. the volume shrinkage of the methacrylate monomers used that occurs during the polymerization process, which can lead, for example, to the formation of very unfavorable edge gaps in the case of filling composites and negatively affect the dimensional stability in the case of prosthetic materials (ΔV in the case of pure MMA) P is, for example, 21.0% by volume).
[0005] Another disadvantage of PMMA or dimethacrylate polymers is the high brittleness of the material. Low fracture toughness is an intrinsic property of amorphous PMMA glasses and, in the case of polymer networks formed from dimethacrylate mixtures, is primarily caused by their very irregular network structure.
[0006] In recent years, additive manufacturing methods have attracted increasing attention and are widely used for the production of dental moldings. In additive manufacturing methods, which are also called generative manufacturing methods, 3D moldings are generated starting from a CAD data set in layers of polymerizable materials, wherein the layers are cured by controlled exposure to light. In stereolithography (SL), UV lasers are used as light sources. In the DLP method (digital light processing), a projectable image is used to cure the photopolymerizable resin in the layers.
[0007] In view of the characteristics of this method, the building materials used for additive manufacturing of dental moldings must meet various requirements. They should have low viscosity and high transparency and good mechanical properties after curing. The materials disclosed in the prior art are optimized for specific properties, often at the expense of other properties.
[0008] The use of monofunctional and polyfunctional methacrylates as resins for additive processes is the subject of numerous patents and patent applications.
[0009] US 10,562,995 B2 discloses polymer resins for stereolithographic production of dental prostheses based on mixtures of aromatic di(meth)acrylates free of OH or COOH groups and (meth)acrylic monomers containing at least one OH or COOH group.
[0010] US 10,568,814 B2 discloses a photopolymerizable composition for manufacturing artificial teeth and denture bases by 3D printing, which is said to have high flexural strength and high elastic modulus after curing. The material is based on a mixture of ethoxylated bisphenol A dimethacrylate, monofunctional methacrylate and urethane dimethacrylate.
[0011] EP 3 020 361 A1 relates to a curable composition for use in additive manufacturing processes, comprising free-radically polymerizable polysiloxanes and disiloxanes. The material is said to be characterized by high dimensional stability and improved biocompatibility.
[0012] EP 3 494 954 A1 discloses a photopolymerizable composition for producing dental prostheses, comprising a mixture of an aromatic acrylate having a molar mass of 200 to 800 g / mol and at least one other (meth)acrylate, which may contain aromatic and non-aromatic rings. The material is said to be characterized by good Charpy fracture toughness.
[0013] EP 3 564 206 A1 discloses (meth)acryloyloxy-substituted benzoic acid esters which are said to be suitable as reactive diluents for additive manufacturing processes.
[0014] Dental moldings must have good fracture toughness and at the same time good flexural strength and a high modulus of elasticity. An improvement in fracture toughness can be achieved by internal plasticization, for example by adding flexible monomers. The disadvantage of these methods is that they significantly reduce the flexural strength and modulus of elasticity of the polymer. According to the prior art, polymer particles with a core-shell structure that result in relatively good flexural strength and a relatively high modulus of elasticity are therefore usually added to polymer resins as so-called impact modifiers to improve fracture toughness.
[0015] WO 2014 / 078537 A1 discloses a resin mixture for producing dental moldings by a 3D printing method based on monofunctional and polyfunctional methacrylates, which contains an impact modifier based on silicone acrylates with a core-shell structure for improving impact resistance and fracture toughness.
[0016] US 2018 / 0000570 A1 relates to a building material based on monofunctional and multifunctional (meth) acrylates for additive manufacturing of dental parts. The building material comprises silicone acrylate-based rubber particles (product S2006 from Mitsubishi Rayon Co.) with a core-shell structure as an impact modifier and an oligomer, which is prepared by reacting 1,6-trimethyl diisocyanate, bisphenol A propoxylate and 2-hydroxyethyl methacrylate (HEMA). The cured parts are said to have good mechanical and physical properties and good biocompatibility.
[0017] US 10,299,896 B2 and US 2019 / 0053883 A1 disclose dental parts manufactured by an additive method, which have at least two layers of building materials with different compositions. One layer is formed by a material comprising an oligomer, which is obtained by reacting an intermediate product having a terminal isocyanate group with a hydroxyl-based methacrylate, a polymerizable acrylic compound and an impact modifier. At least one other layer is formed by a material comprising a urethane monomer, ethylene glycol dimethacrylate and a filler. It is said that the combination of materials with different mechanical and physical properties is beneficial for adapting the parts to different requirements. Commercially available polymers with a core-shell structure, such as, for example, the product M570 from Kaneka, are used as impact modifiers.
[0018] EP 3 564 282 A1 discloses curable compositions for high temperature photopolymerization processes, comprising oligomeric urethane dimethacrylates as glass transition temperature modifiers, (poly)carbonate-(poly)urethane dimethacrylates as toughness modifiers and optionally core-shell particles. They are said to have good thermomechanical properties and good biocompatibility and are suitable for the manufacture of orthodontic appliances.
[0019] The mode of action of the impact modifier with core-shell structure is based on the interaction between the tip and the core-shell polymer particles that form the crack. These particles have a relatively soft polymer core and a hard polymer shell. If the crack tip encounters such particles, a cavity is formed in the core, and the polymer shell is separated from the polymer resin matrix, and the core is separated from the shell, and thus a space (cavitation) for plastic deformation surface is formed. The major disadvantage of dental applications is that core-shell polymers (CSP) significantly reduce the transparency of the material, which has an adverse effect on the stereolithography construction method. Summary of the invention
[0020] The object of the present invention is to provide materials for producing dental moldings which have a property profile optimized for additive methods. In particular, the materials should have high transparency as well as good fracture toughness and high fracture work. In addition, they should exhibit low viscosity and good mechanical properties after storage in water as well as good biocompatibility.
[0021] According to the invention, this object is achieved by a free-radically polymerizable dental material comprising at least one ABA or AB block copolymer. In addition, the dental material preferably comprises at least one monofunctional free-radically polymerizable monomer (a) and preferably also at least one free-radically polymerizable urethane di(meth)acrylate telechelic (b).
[0022] The dental material according to the invention preferably has the following composition:
[0023] (a) 30 to 70% by weight, preferably 30 to 61% by weight and particularly preferably 40 to 60% by weight of at least one aromatic, bicyclic or tricyclic mono(meth)acrylate,
[0024] (b) 20 to 60% by weight, preferably 30 to 55% by weight and particularly preferably 33 to 55% by weight of at least one urethane di(meth)acrylate telechelic having a number-average molar mass of 750 to 2000 g / mol,
[0025] (c) 0 to 30% by weight, preferably 0 to 20% by weight, and particularly preferably 0% by weight of a di(meth)acrylate monomer(s),
[0026] (d) 1 to 12% by weight, preferably 2 to 12% by weight, and particularly preferably 2 to 10% by weight, of at least one ABA and / or AB block copolymer, in which the mixture of one or more A blocks is homogeneously miscible with the mixture of components (a) to (c), and the mixture of B blocks with components (a) to (c) is inhomogeneously miscible, and
[0027] (e) 0.1 to 5.0% by weight, preferably 0.2 to 4.0% by weight and particularly preferably 0.3 to 3.0% by weight of at least one initiator for free-radical polymerization.
[0028] Unless otherwise stated, all weight percentages herein are related to the total mass of the material.
[0029] The dental material according to the invention preferably comprises as component (a) at least one aromatic, bicyclic or tricyclic mono(meth)acrylate of the formula (I)
[0030]
[0031] where the variables have the following meanings:
[0032] A is an aromatic group having 6 to 15 carbon atoms or a bicyclic or tricyclic aliphatic group having 7 to 10 carbon atoms, wherein A may be unsubstituted or substituted by one or more C1-C5 alkyl groups, C1-C5 alkoxy groups and / or chlorine atoms;
[0033] R is hydrogen or methyl;
[0034] X 1 , X 2 is in each case independently of one another absent or an ether, ester or urethane group, wherein if Y 1 If it does not exist, then X 1 does not exist, and if Y 2 If it does not exist, then X 2 does not exist;
[0035] Y 1 , Y 2 In each case independently of one another is absent or is a branched or preferably straight-chain aliphatic hydrocarbon radical having 1 to 10 carbon atoms, which may be interrupted by 1 to 3 oxygen atoms.
[0036] In this context, (meth)acrylate means acrylate, methacrylate or mixtures thereof, with methacrylate being preferred in each case.
[0037] All formulas shown herein extend only to those compounds that are compatible with the chemical valence theory. The indication that a group is interrupted by, for example, one or more oxygen atoms is understood to mean that these atoms are inserted into the carbon chain of the group in each case. Therefore, these atoms have C atoms adjacent on both sides and cannot be terminal. C1 groups cannot be branched or interrupted. Corresponding to the usual nomenclature, aromatic hydrocarbon groups also refer to those groups that contain aromatic and non-aromatic groups. Preferred aromatic groups are, for example, 2,2-diphenylpropane.
[0038] The preferred, particularly preferred and very particularly preferred definitions given for the individual variables can be selected in each case independently of one another. According to the invention, compounds in which all variables have preferred, particularly preferred and very particularly preferred definitions are naturally particularly suitable.
[0039] Preferred aromatic radicals A are benzene, biphenyl and 2,2-diphenylpropane:
[0040]
[0041] Preferred bicycloaliphatic radicals A are bicyclo[4.4.0]decane, bicyclo[4.3.0]nonane, bicyclo[2.2.2]octane and bicyclo[2.2.1]heptane:
[0042]
[0043] Preferred tricyclic aliphatic groups A are tricyclic [5.2.1.0 2,6 ]Decane:
[0044]
[0045] Preferred aromatic mono(meth)acrylates (a) are 2-phenoxyethyl(meth)acrylate, 2-(o-biphenyloxy)ethyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, 2[(benzyloxycarbonyl)-amino]-ethyl(meth)acrylate, 2-[(benzylcarbamoyl)-oxy]-ethyl(meth)acrylate, 1-phenoxyprop-2-yl(meth)acrylate and 2-(p-cumylphenoxy)-ethyl(meth)acrylate. Particularly suitable aromatic mono(meth)acrylates are 2-phenoxyethyl(meth)acrylate, 2-(o-biphenyloxy)ethyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, 2-[(benzyloxycarbonyl)amino]ethyl(meth)acrylate, 1-phenoxyprop-2-yl(meth)acrylate, 2-(benzyloxy)ethyl(meth)acrylate, 3-phenoxybenzyl(meth)acrylate, phenoxypropyl(meth)acrylate, 2-benzyloxyethyl(meth)acrylate, 2-benzoyloxyethyl(meth)acrylate, methyl 2-(meth)acryloyloxybenzoate, 2-phenylethyl(meth)acrylate and / or 2-(p-cumylphenoxy)ethyl(meth)acrylate.
[0046] Preferred bicyclic or tricyclic mono(meth)acrylates (a) are tricyclodecyl(meth)acrylate, tricyclodecylmethyl(meth)acrylate and in particular 4,7,7-trimethylbicyclo[2.2.1]heptyl(meth)acrylate.
[0047]
[0048] The aromatic, bicyclic or tricyclic monomethacrylates of formula (I) used according to the invention are characterized by good free radical polymerizability. In addition, the polymers of these monomethacrylates have relatively low polymerization shrinkage and good mechanical properties. Due to their relatively high molar mass (150 to 350 g / mol) and their relatively nonpolar structure, the mono(meth)acrylates of formula (I) also have low volatility and relatively low viscosity.
[0049] The dental material according to the invention comprises as component (b) at least one urethane dimethacrylate telechelic compound having a molar mass of 750 to 2000 g / mol. Component (b) comprises two free-radically polymerizable groups and therefore acts as a crosslinker during the polymerization of the material according to the invention, that is, it leads to the formation of a polymer network. Due to the relatively high molar mass of component (b), polymers with a low network density and a low polymerization shrinkage are obtained.
[0050] Unless otherwise indicated, the molar masses of oligomers and polymers herein are number-average molar masses, the absolute values of which can be determined using known methods of freezing point depression (freezing point depression method), boiling point elevation (boiling point determination method) or by the reduction of the vapor pressure (vapor pressure osmotic pressure method). The number-average molar mass of oligomers and polymers is preferably determined by means of gel permeation chromatography (GPC). This is a relative method in which molecules are separated according to their size, more specifically according to their hydrodynamic volume. The absolute molar mass is determined by calibration with a known standard.
[0051] The urethane dimethacrylate telechelic compound (b) is preferably obtained by reacting a diisocyanate with a diol (HO-DA-OH) and then reacting an α,ω-isocyanate-functionalized urethane telechelic compound with HEMA or HPMA. DA preferably represents an aromatic or aliphatic hydrocarbon radical having 6 to 33 carbon atoms, preferably a divalent polycyclic hydrocarbon radical, in particular an o-diphenyl, p-diphenyl or bisphenol A radical, or a branched or preferably straight-chain C2-C 18 Alkylene groups. The hydrocarbon group may contain one or more O atoms and / or S atoms, with O atoms being preferred.
[0052] Preferred diols of the formula HO-DA-OH are ethoxylated or propoxylated bisphenol A, o- or p-diphenyl and C2-C 18 Alkanediols, which may contain 1 to 4 O or S atoms in the carbon chain. Particularly preferred diols are ethoxylated or propoxylated bisphenol A, hexane-1,6-diol, octane-1,8-diol, nonane-1,9-diol, decane-1,10-diol or dodecane-1,12-diol, tetraethylene glycol or pentaethylene glycol having 2, 3 or 4 ethoxy or propoxy groups. Ethoxylated or propoxylated bisphenol A, decanediol, undecanediol or dodecanediol and cyclic or polycyclic aliphatic diols having 2 or 3 ethoxy or propoxy groups, in particular cyclohexanediol, norbornanediol, tricyclodecanediol and tricyclodecane dimethanol (octahydro-4,7-methylene-1H-indenedimethanol) are very particularly preferred.
[0053] Preferred diisocyanates are hexamethylene-1,6-diisocyanate (HMDI), 2,2,4-trimethylhexamethylene-1,6-diisocyanate (TMDI), 1-isocyanato-3-isocyanatomethyl-3,5,5-trimethylcyclohexane (isophorone diisocyanate, IPDI), m-tetramethylxylylene diisocyanate (1,3-bis(2-isocyanato-2-propyl)benzene, TMXDI), toluene-2,4-diisocyanate (TDI), diphenylmethane-4,4′-diisocyanate (MDI) and 1-isocyanato-4-[(4-isocyanatocyclohexyl)methyl]cyclohexane (H12MDI), among which IPDI is particularly preferred.
[0054] According to the present invention, telechelic compounds according to the general formula (II) are preferred
[0055]
[0056] where the variables have the following meanings:
[0057] R 1 , R 2 in each case independently of one another is H or methyl, preferably methyl,
[0058] R 3 , R 4 in each case independently of one another is H or methyl, preferably methyl,
[0059] x, y are in each case independently of one another an integer from 1 to 11, preferably from 1 to 5,
[0060] n is 1, 2 or 3, preferably 1
[0061] Z is
[0062]
[0063] Preferred:
[0064]
[0065] DA is a structural element which is derived from the diol HO-DA-OH by cleaving hydrogen atoms from two hydroxyl groups.
[0066] The urethane dimethacrylate telechelics preferred according to the invention are characterized by good free-radical polymerizability. In addition, they impart good cohesive properties to the cured material.
[0067] The monofunctional methacrylate (a), the urethane dimethacrylate telechelic compound (b) and optionally other free-radically polymerizable monomers are preferably used in such a proportion that a network density below v c=300 to 5000 mol / m 3 , particularly preferably 400 to 3000 mol / m 3 The crosslinking density is essentially determined by the ratio of the crosslinking monomer to the monofunctional monomer. According to the invention, dental materials in which the mole fraction of the crosslinking monomer is in the range of 0.1 to 0.6, and particularly preferably 0.15 to 0.45, are preferred. All radically polymerizable components of the material according to the invention are used to calculate the mole fraction, i.e. in particular components (a) to (c) and optionally further radically polymerizable monomers. Crosslinking monomers are all radically polymerizable components having two or more radically polymerizable groups, i.e. in particular components (b) and (c). Crosslinking monomers are also referred to as multifunctional monomers. Monofunctional monomers are monomers having only one radically polymerizable group.
[0068] The network density corresponds to the number of nodes per unit volume (in mol) and can be calculated from the plateau value of the storage modulus G' in the elastic region by dynamic mechanical measurements. g and network density ν c The determination is carried out using a rheometer, preferably an Anton Paar MCR301 rheometer. For this purpose, the storage modulus and loss modulus of test pieces (25x5x1 mm, clamped longitudinally) are measured between 25° C. and 250° C. (frequency 1 Hz, deformation 0.05%, heating rate 2 K / min). g It is the maximum value of the loss factor tanδ (ratio of loss modulus to storage modulus). The network density is calculated according to the formula ν c =G' / (RT) calculation, where G' is T g The storage modulus at +50K, R is the universal gas constant, T is T g Temperature at +50K, in Kelvin.
[0069] In order to further set the crosslinking density and to influence the mechanical properties of the polymer, the dental material according to the invention may comprise further di(meth)acrylate monomers (c) in addition to components (a) and (b).
[0070] Preferred di(meth)acrylates (c) are bisphenol A dimethacrylate (bis-GMA, addition product of methacrylic acid and bisphenol A diglycidyl ether), ethoxylated or propoxylated bisphenol A dimethacrylates, such as, for example, bisphenol A dimethacrylate SR-348c (Sartomer) having 3 ethoxy groups, 2,2-bis[4-(2-methacryloyloxypropoxy)phenyl]propane (UDMA, addition product of HEMA and TMDI), V380 (addition product of a mixture of 0.7 mol of 2-hydroxyethyl methacrylate and 0.3 mol of 2-hydroxypropyl methacrylate with 1 mol of α,α,α′,α′-tetramethyl-m-xylene diisocyanate), bis(methacryloyloxymethyl)tricyclo-[5.2.1.0 2,6 ]decane (DCP), di-, tri- or tetraethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetra(meth)acrylate, as well as glycerol dimethacrylate and glycerol trimethacrylate, 1,4-butanediol dimethacrylate, 1,10-decanediol dimethacrylate (D3MA) and 1,12-dodecanediol dimethacrylate.
[0071] The di(meth)acrylate monomers (c) are characterized by a relatively low molar weight. According to the invention, di(meth)acrylates (c) having a molar weight of 200 to 800 g / mol, preferably 220 to 650 g / mol, are preferred. Due to the low molar weight compared to the urethane di(meth)acrylate telechelic (b), the di(meth)acrylate monomers (c) cause relatively strong crosslinking of the polymer, thus resulting in a high network density, which can have an adverse effect on the fracture toughness. The proportion of other di(meth)acrylates is therefore limited to a maximum of 30% by weight, preferably a maximum of 10% by weight. According to a particularly preferred embodiment, the dental material according to the invention contains only urethane di(meth)acrylate telechelic (b) as crosslinking agent.
[0072] Furthermore, the dental material according to the invention may contain other mono(meth)acrylates in addition to component (a). The proportion of other mono(meth)acrylates is preferably less than 10% by weight, with materials containing no other mono(meth)acrylates being particularly preferred.
[0073] The dental material according to the invention comprises as component (d) at least one ABA and / or one AB block copolymer.Block copolymers are macromolecules consisting of two or more homopolymer blocks which are covalently bonded to one another.
[0074] The block copolymers preferred according to the invention can be prepared using known living or controlled polymerization methods, for example by free radical or ionic (anionic and cationic) polymerization, wherein controlled free radical polymerization and living anionic polymerization are preferred. However, block copolymers can also be obtained by coupling the end groups of homopolymers. The block copolymers used according to the invention can exist as diblock and triblock copolymers.
[0075] AB block copolymers can be prepared, for example, by coupling the A blocks with terminal OH groups by esterification with B blocks having COOH groups. End-group-functionalized homopolymer blocks can be prepared relatively easily using methods of controlled free radical polymerization or by endcapping in the case of anionic polymerization.
[0076] For example, monomer A is anionically polymerized and an OH group is inserted by end-capping. The OH end groups can then be esterified, for example, with α-bromoisobutyrate. The bromine end groups obtained in this process are then used as starting centers for forming B blocks by ATRP (atom transfer radical polymerization) of monomer B initiated by metal complexes such as Cu(I), Ru(I) or Fe(II).
[0077] Triblock copolymers can be prepared similarly. For example, the B block is prepared via a dianionic mechanism by anionic polymerization of monomer B. The formed B midblock carries anionic end groups on each side, which initiate anionic polymerization of monomer A to form two A blocks (method 1). In each case, the esterification of the telechelic B block with suitable functional groups such as OH groups at both ends and the two A blocks functionalized only on one side such as with COOH groups produces an ABA triblock copolymer (method 2). Finally, the OH-telechelic homopolymer of monomer B can be esterified with α-bromoisobutyrate. The two bromine end groups thus formed in the homopolymer block B can then be used as the starting center for forming two A blocks by ATRP (method 3).
[0078] It is also possible to insert terminal or pendant polymerizable methacrylate groups during the synthesis of the block copolymers. These lead to better integration of the block copolymers into the polymer network formed by free-radical copolymerization of the methacrylate groups.
[0079] The monomers are preferably selected so that the A blocks are miscible with the resin matrix, ie, miscible with the mixture of components (a) to (c), and the B blocks are immiscible with the resin matrix.
[0080] Here, miscibility refers to the state relative to a single phase in the thermodynamic sense. Accordingly, a miscible polymer block is a polymer block consisting of monomers, the homopolymer of which is soluble in the resin matrix, so that the mixture has a transparency of at least 95%. In contrast, if the mixture is turbid or opaque, i.e., the transparency is less than 95%, the homopolymer and therefore the corresponding polymer block is not miscible with the resin matrix. Transparency is measured as transmittance (D65) according to ISO 10526:1999 standard using a spectrophotometer, such as a Konika-Minolta CM-5 spectrophotometer, on a 1 mm thick test piece polished to high gloss.
[0081] The block copolymers bring about a significant improvement in the fracture toughness of the material according to the invention after curing. It is assumed that the immiscibility of the B block of the block copolymer with the remaining components of the composition according to the invention brings about microphase separation and thus forms a morphology at the nanoscale level. Here, the macromolecules of the ABA or AB block copolymers form spherical or worm-like phases in the monomer resin or are formed by self-assembly during the curing process, and these phases can interact with the crack tip, that is to say, the crack tip meets these phases and the fracture energy is distributed into the phases so that the crack does not migrate further through the material and does not increase in size. The growth of cracks in transparent materials can be observed under an electron microscope. In fracture mechanics, the frontmost part of the crack is called the crack tip.
[0082] Preferred block copolymers according to the invention are AB diblock and ABA triblock copolymers.
[0083] The A block is a polymer, preferably an oligomer, which consists of one or more of the following monomers: cyclic, aliphatic esters or ethers, arylene oxides, alkylene oxides, free-radically polymerizable monomers, such as α,β-unsaturated acids and α,β-unsaturated acid esters. The A block is preferably a poly(meth)acrylate oligomer, a polylactone oligomer, a phenylene ether oligomer or a polyalkylene oxide oligomer. Very particularly preferably, the A block is a polymer of caprolactone, 2,6-dialkyl-1,4-phenylene ether, and in particular a polymer of 2,6-dimethyl-1,4-phenylene ether, ethylene oxide, propylene oxide or (meth)acrylate. Therefore, the A block is preferably a polycaprolactone (PCL) oligomer, a poly(2,6-dimethyl-1,4-phenylene ether) oligomer, a poly(ethylene oxide) oligomer, a poly(propylene oxide) oligomer or a poly(meth)acrylate oligomer.
[0084] The B block is preferably a polysiloxane oligomer and / or a polyvinyl oligomer and / or a polyolefin oligomer and / or a polydiene oligomer. Particularly preferably, the B block is a polydiene oligomer, a polyalkanoic acid vinyl ester oligomer or a polyolefin oligomer according to the formula -O-(SiR 5 2-O) p - a polysiloxane oligomer, wherein
[0085] R 5 It is a straight chain C1-C 20 Alkyl, branched C3-C 12 Alkyl or C6-C 20 An aryl group in which each R 5 The groups may be the same or different, and
[0086] p is a number of 3-100, preferably a number of 10-50.
[0087] Very particularly preferably, the B block is a polymer of dimethylchlorosilane, cyclotridimethoxysilane or cyclotetradimethoxysilane, isoprene, vinyl acetate, isobutylene, cis-butadiene or ethylene. The B block is therefore preferably a poly(dimethylsiloxane) (PDMS) oligomer, a poly(isoprene) oligomer, a poly(vinyl acetate) oligomer, a poly(isobutylene) oligomer, a cis-poly(butadiene) oligomer or a poly(ethylene) oligomer.
[0088] The B block is characterized by relatively high flexibility. The soft block refers to a block formed from a monomer whose homopolymer has a glass transition temperature T G Below 50° C., preferably below 0° C., very particularly preferably in the range from −30 to −110° C. Block copolymers with soft blocks improve the fracture toughness but impair the flexural strength and elastic modulus of the polymer much less than internal plasticizers.
[0089] Preference is given according to the invention to polyester-polysiloxane block copolymers according to the following general formula:
[0090] (PCL) q -b-(PDMS) r -b-(PCL) q
[0091] in
[0092] q is in each case a number from 5 to 40, preferably from 10 to 20, and
[0093] r is a number of 10-100, preferably 30-60.
[0094] (PCL) q represents polycaprolactone, which is composed of q caprolactone monomers, (PDMS) r represents poly(dimethylsiloxane), which is composed of r dimethylsiloxane monomers. The letter b represents a block.
[0095] Preference is further given to poly(meth)acrylate-polysiloxane block copolymers which comprise polymethyl methacrylate groups as A blocks and polysiloxane groups as B blocks, the polysiloxane groups preferably being as defined above and very particularly preferably poly(dimethylsiloxane) groups.
[0096] Particularly preferably, the ABA triblock copolymers are PCL-b-PDMS-b-PCL and PMMA-b-PDMS-b-PMMA in a molar ratio A:B of 0.1 to 5 and a molar mass of preferably 3 to 25 kDa, particularly preferably 4 to 20 kDa, very particularly preferably 5 to 10 kDa. Preferred block copolymers are PCL-b-PDMS-b-PCL, where the molar mass of the PDMS block is about 3200 g / mol and the molar mass of the PCL block is in each case about 1600 g / mol. PCL stands for polycaprolactone, PDMS stands for poly(dimethylsiloxane) and PMMA stands for polymethyl methacrylate.
[0097] The block copolymer or block copolymers are preferably used in an amount of 1 to 12% by weight, particularly preferably in an amount of 2 to 10% by weight, very particularly preferably in an amount of 3 to 8% by weight, relative to the total weight of the dental material.
[0098] The block copolymer used according to the present invention is found to significantly improve the fracture toughness of the polymer network without compromising transparency. In addition, they only bring a relatively small viscosity increase. Another advantage of the block copolymer used according to the present invention is that they can easily be uniformly mixed with the remaining components of the material, and the uniform dispersion of core-shell polymer particles is much more complicated. In addition, particles tend to settle, and the composition based on core-shell particles is not too stable as a result. On the other hand, block copolymers can be well incorporated in the resin mixture, and the result can make the material match the application of the plan, and set the fracture toughness and fracture work of expectation without any problem.
[0099] The dental material according to the invention comprises as component (e) at least one initiator for free-radical polymerization, preferably a photoinitiator.
[0100] Preferred photoinitiators are benzophenone, benzoin and their derivatives and α-diketones and their derivatives, such as 9,10-phenanthrenequinone, 1-phenyl-propane-1,2-dione, diacetyl or 4,4′-dichlorobenzil. Particular preference is given to using camphorquinone (CQ) and 2,2-dimethoxy-2-phenyl-acetophenone, and very particular preference is given to using α-diketones in combination with amines as reducing agents, such as, for example, 4-(dimethylamino)benzoate (EDMAB), N,N-dimethylaminoethyl methacrylate, N,N-dimethyl-sym-xylidine or triethanolamine. For the visible range, preferred unimolecular photoinitiators are monoacyltrialkylgermanium, diacyldialkylgermanium and tetraacylgermanium and tetraacylstannanes, such as, for example, benzoyltrimethylgermanium, dibenzoyldiethylgermanium, bis(4-methoxybenzoyl)-diethylgermanium, tetra(2-methylbenzoyl)germane or tetra( Mixtures of different photoinitiators can also be used, such as, for example, bis(4-methoxybenzoyl)diethylgermanium in combination with camphorquinone and ethyl 4-dimethylaminobenzoate.
[0101] Preferred initiators for curing the dental material according to the invention with UV light are Norrish type I photoinitiators, in particular acetophenones such as 2,2-diethoxy-1-acetophenone, benzoin ethers such as Irgacure 651 (benzil dimethyl ketal), hydroxyalkylphenylacetophenones such as Irgacure 184 (1-hydroxycyclohexyl phenyl ketone), acyl or bisacylphosphine oxides such as Irgacure TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide) and Irgacure 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide). Further preferred photoinitiators are 2-benzyl-2-(dimethylamino)-4′-morpholinobutyrophenone (Irgacure 369) and 1-butanone-2-(dimethylamino)-2-(4-methylphenyl)methyl-1-4-(4-morpholino)phenyl (Irgacure 379). Particularly preferred photoinitiators are bis(4-methoxybenzoyl)diethylgermanium, Irgacure TPO and Irgacure 819 and camphorquinone / 4-(dimethylamino)benzoate. For post-tempering, it is advantageous to use two photoinitiators that differ in their absorption range, such as, for example, Irgacure TPO and camphorquinone / 4-(dimethylamino)benzoate.
[0102] The dental material according to the invention may alternatively or additionally also contain a thermal initiator, for example an azo compound, such as 2,2'-azobis(isobutyronitrile) (AIBN) or azobis-(4-cyanovaleric acid), or a peroxide, such as dibenzoyl peroxide, dilauroyl peroxide, tert-butyl peroctanoate, tert-butyl perbenzoate or di-(tert-butyl) peroxide. Combinations with aromatic amines can also be used to accelerate initiation with the aid of peroxides. Preferred redox systems are combinations of dibenzoyl peroxide with amines, such as N,N-dimethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, ethyl p-dimethylaminobenzoate or structurally related systems.
[0103] The initiator or initiators are preferably used in a total amount of 0.1 to 5.0% by weight, particularly preferably 0.2 to 4% by weight and very particularly preferably 0.3 to 3.0% by weight, these amounts including all initiator components such as, for example, reducing agents.
[0104] In order to further improve the fracture toughness and impact resistance, the dental material according to the invention may also contain a certain proportion of one or more core-shell polymers (component (f)). Core-shell polymers (CSP) having a soft polymer core, for example consisting of crosslinked butyl acrylate, and a relatively hard polymer shell, for example PMMA, are preferred. Soft or flexible polymers are those having a glass transition temperature T G Polymers with a T of about -110°C and a T of about -50°C are preferred. G PDMS is a preferred specific example. A hard polymer refers to a polymer having a glass transition temperature higher than 50°C, preferably higher than 80°C. G PMMA is a preferred specific example.
[0105] The fracture toughness modification of the CSP particles in the free radical dimethacrylate polymer network depends primarily on the type of CSP particles, the particle size, the crosslinking density and the core-to-shell weight ratio, which is preferably in the range of 1:1 to 200:1. The crosslinking density is essentially determined by the proportion of crosslinking monomers in the particle core. This is preferably in the range of 1 to 10% by weight relative to the mass of the core. According to the invention, particles with a particle size of 0.20 to 5.0 μm are preferred.
[0106] Preferred according to the invention are CSP particles having a core made of a soft plastic such as polybutadiene, polyisoprene, polybutyl acrylate, MMA-butadiene-styrene copolymer (MBS) or polydimethylsiloxane and a shell made of a hard plastic such as PMMA or MMA-styrene copolymer. CSP particles suitable according to the invention are commercially available, for example from Arkema (Clearstrength), Soken (Chemisnow) or Kaneka (e.g. M521 or M210).
[0107] Core-shell polymers can be added in an amount of up to 15% by weight. The disadvantage of using core-shell polymers is that they greatly impair the transparency of the composition, which has a negative impact on the depth of cure in the case of photopolymerization and also has a negative aesthetic effect in the case of dental moldings. According to the invention, materials containing up to 5% by weight and particularly preferably no core-shell particles are therefore preferred. When CSP particles are incorporated into dental materials, good dispersion is to be ensured.
[0108] In order to influence the mechanical properties, the dental materials according to the invention can be reinforced with inorganic particulate fillers (g).
[0109] Preferred inorganic fillers are oxides such as SiO2, ZrO2 and TiO2 or mixed oxides of SiO2, ZrO2, ZnO and / or TiO2, nanoparticles or fine fillers such as fumed silica or precipitated silica, glass powders such as quartz, glass ceramics, borosilicates or radiopaque glass powders, preferably barium or strontium aluminosilicate glasses, and radiopaque fillers such as ytterbium trifluoride, tantalum (V) oxide, barium sulfate, or mixed oxides of SiO2 and ytterbium (III) oxide or tantalum (V) oxide. The dental material according to the invention may also contain fibrous fillers, nanofibers, whiskers or mixtures thereof. According to a preferred embodiment, the material according to the invention does not contain fluoroaluminosilicate glass, calcium aluminosilicate glass or other fillers that react with organic acids in the sense of acid-base reactions.
[0110] Preferably, the particle size of the oxide is 0.010 to 15 μm, the particle size of the nanoparticles or fine fillers is 10 to 300 nm, the particle size of the glass powder is 0.01 to 15 μm, preferably 0.2 to 1.5 μm, and the particle size of the radiopaque filler is 0.2 to 5 μm.
[0111] Particularly preferred fillers are mixed oxides of SiO2 and ZrO2 with a particle size of 10 to 300 nm, glass powders with a particle size of 0.2 to 1.5 μm, in particular radiopaque glass powders such as barium or strontium aluminosilicate glass, and radiopaque fillers with a particle size of 0.2 to 5 μm, in particular mixed oxides of ytterbium trifluoride and / or SiO2 and ytterbium(III) oxide.
[0112] In order to improve the bond between the filler particles and the crosslinked polymeric matrix, SiO2-based fillers can be surface-modified with methacrylate-functionalized silanes. A preferred example of such a silane is 3-methacryloxypropyl-trimethoxysilane. For surface modification of non-silicate fillers such as ZrO2 or TiO2, functionalized acidic phosphates such as, for example, 10-methacryloxydecyl dihydrogen phosphate can also be used.
[0113] Further preferred fillers are particulate waxes, in particular carnauba wax, preferably with a particle size of 1 to 10 μm, uncrosslinked or partially crosslinked polymethyl methacrylate (PMMA) particles, preferably with a particle size of 500 nm to 10 μm, and polyamide-12 particles, preferably with a particle size of 5 to 10 μm.
[0114] Furthermore, the dental material according to the invention may contain so-called prepolymer fillers or isofillers, i.e. ground composite materials preferably with a broad particle size distribution, for example with a particle size of 0.05 to 20 μm, in particular about 0.1 to about 10 μm. The prepolymer fillers or isofillers are preferably surface-modified, in particular silanized.
[0115] Unless otherwise stated, all particle sizes herein are weight-average particle sizes, wherein the particle size determination in the range of 0.1 μm to 1000 μm is carried out by static light scattering, preferably using a LA-960 static laser scattering particle size analyzer (Horiba, Japan). Here, a laser diode with a wavelength of 655 nm and an LED with a wavelength of 405 nm are used as light sources. The use of two light sources with different wavelengths makes it possible to measure the entire particle size distribution of the sample in only one measurement process, wherein the measurement is carried out as a wet measurement. For this purpose, a 0.1 to 0.5% aqueous dispersion of filler is prepared and its scattered light is measured in a flow cell. The scattered light analysis for calculating the particle size and particle size distribution is carried out according to DIN / ISO 13320 using the Mie theory.
[0116] Particle sizes below 0.1 μm are preferably determined by means of dynamic light scattering (DLS). Particle size measurements in the range of 5 nm to 0.1 μm are preferably carried out at 25° C. at a scattering angle of 90° by dynamic light scattering (DLS) of aqueous particle dispersions, preferably using a Malvern Zetasizer Nano ZS (Malvern Instruments, Malvern UK) with a He-Ne laser at a wavelength of 633 nm.
[0117] Light scattering decreases with decreasing particle size. Particle sizes below 0.1 μm can also be determined by means of SEM or TEM spectroscopy. Transmission electron microscopy (TEM) is preferably performed using a Philips CM30 TEM at an accelerating voltage of 300 kV. To prepare the sample, a drop of the particle dispersion is applied to a carbon-coated The solution was then deposited on a thick copper grid (mesh size 300) and the solvent was evaporated.
[0118] Fillers are divided into macrofillers and microfillers according to their particle size, wherein fillers with an average particle size of 0.2 to 10 μm are called macrofillers, and fillers with an average particle size of about 5 to 100 nm are called microfillers. Macrofillers are obtained, for example, by grinding quartz, radiopaque glass, borosilicate or ceramics and are usually composed of fragmentary parts. Gas-phase SiO2 or precipitated silica, or mixed oxides such as SiO2-ZrO2, obtainable by hydrolysis co-condensation of metal alkoxides, are preferably used as microfillers. Microfillers preferably have an average particle size of about 5 to 100 nm. Fillers with small particle sizes have a greater thickening effect.
[0119] In a preferred embodiment, the dental material according to the invention comprises a mixture of two or more fillers, in particular two or more fillers with different particle sizes. It was found that the use of such a filler mixture does not excessively increase the viscosity of the material, so that the composition can be processed well using additive methods such as, for example, using stereolithography. The total filler content is preferably in the range of 0 to 20% by weight, particularly preferably in the range of 0 to 10% by weight.
[0120] The dental material according to the invention may also contain one or more UV absorbers (h). During the light-induced curing of the composition according to the invention, the UV absorbers serve to reduce the penetration depth of the light and thus the depth of polymerization. This proves to be advantageous in particular in the case of stereolithography applications, since only thin layers are to be cured in stereolithography. The use of UV absorbers can improve the precision of the stereolithography method.
[0121] UV absorbers based on benzotriazole, benzophenone or triazine are preferred. Particularly preferred UV absorbers are 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol], 2,2',4,4'-tetrahydroxybenzophenone, 2-tert-butyl-6-(5-chloro-2H-benzotriazol-2-yl)-4-methylphenol (bumetriazolyl), 2,2'-benzene-1,4-diylbis(4H-3,1-)benzoxazin-4-one), 2-(4,6-bis-(2,4-dimethylbenzene) ... 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2,2'-dihydroxy-4-methoxybenzophenone and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone. So-called hindered amine light stabilizers such as bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, methyl-1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate and bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1)-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate are further preferred. Quite particularly preferred UV absorbers are bumetriazole and 2,2',4,4'-tetrahydroxybenzophenone.
[0122] The UV absorber preferably has a maximum absorption corresponding to the wavelength of the light used for curing. UV absorbers with a maximum absorption in the range of 320 to 500 nm, preferably 380 to 480 nm are advantageous, with UV absorbers with a maximum absorption below 400 nm being particularly preferred.
[0123] UV absorbers are optionally used in an amount of preferably 0 to 1.0% by weight, particularly preferably 0.01 to 0.5% by weight. Bumetrazole is preferably used in an amount of 0.01 to 0.2% by weight, particularly preferably 0.02 to 0.15% by weight, 2,2',4,4'-tetrahydroxybenzophenone in an amount of 0.01 to 0.07% by weight. All data relate to the total weight of the material. Preference is given to dental materials which do not contain UV absorbers.
[0124] The dental material according to the present invention may also include one or more fluorescent whitening agents (i). According to the present invention, fluorescent whitening agents that absorb light in the UV range, i.e., light with a wavelength lower than 400nm, are preferred. By adding a fluorescent whitening agent, the penetration depth of light can be reduced, thereby reducing the curing depth, and thereby improving the accuracy of the stereolithography method. It is particularly preferred that the light absorbed in the UV range be re-emitted as a fluorescent whitening agent with a wavelength of 400 to 450nm. Such fluorescent whitening agents increase the reactivity of the material because, due to their fluorescence, they emit the absorbed short-wave light as longer-wave blue light, thereby providing additional luminous power for light initiation. According to the present invention, the preferred fluorescent whitening agents are fluorescent agents in the form of 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene and terephthalic acid derivatives, such as, for example, diethyl 2,5-dihydroxyterephthalate or diethyl-2,5-dihydroxyterephthalate.
[0125] One or more fluorescent whitening agents are optionally used in an amount of preferably 0 to 0.1% by weight, particularly preferably 0.001 to 0.05% by weight and very particularly preferably 0.002 to 0.02% by weight, in each case relative to the total weight of the material. Dental materials which do not contain fluorescent whitening agents are preferred.
[0126] Fluorescent whitening agents can be used in combination with UV absorbers. In this case, the weight ratio of UV absorber to fluorescent whitening agent is preferably 2:1 to 50:1, particularly preferably 2:1 to 30:1, and very particularly preferably 2:1 to 5:1 or 10:1 to 25:1. A combination comprising 2,2',4,4'-tetrahydroxybenzophenone or bumetriazole as a UV absorber and 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene as a fluorescent whitening agent is preferred. A combination of 2,2′,4,4′-tetrahydroxybenzophenone and 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene in a weight ratio of 2:1 to 10:1, preferably 2:1 to 5:1, or a combination of bumetriazole and 2,5-bis(5-tert-butyl-benzoxazol-2-yl)thiophene in a weight ratio of 5:1 to 30:1, preferably 10:1 to 20:1, is very particularly preferred.
[0127] The dental materials according to the invention may additionally comprise further additives (j), in particular stabilizers, colorants, plasticizers, thixotropic additives, microbicidal active ingredients and / or foaming agents.
[0128] The dental material according to the invention preferably contains one or more stabilizers. These are free radical scavenging substances which are used to prevent premature polymerization. Stabilizers are also called polymerization inhibitors. Inhibitors or stabilizers improve the storage stability of the material.
[0129] Preferred inhibitors are phenols, such as hydroquinone monomethyl ether (MEHQ) or 2,6-di-tert-butyl-4-methylphenol (BHT). Phenols are preferably used in a concentration of 0.001 to 0.50% by weight. Further preferred inhibitors are phenothiazine, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, galvinoxyl radical, trityl radical and 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) radical. These inhibitors are preferably used in an amount of 0.001 to 0.02% by weight. Polymerization does not occur until these additives are exhausted. These amounts are in each case related to the total mass of the material. Preferably, an inhibitor mixture comprising at least one phenol and at least one other initiator is used.
[0130] In addition, the dental material according to the present invention may also contain a colorant, preferably in a concentration of 0.0001 to 0.5% by weight. Colorants are mainly used for aesthetic purposes. Preferred colorants according to the present invention are organic dyes and pigments, in particular azo dyes, carbonyl dyes, cyanine dyes, azomethine and methine, phthalocyanine and dioxazine. Dyes soluble in the material according to the present invention are particularly preferred, in particular azo dyes. In addition, inorganic and in particular organic pigments that can be well dispersed in the dental material according to the present invention are suitable as colorants. Preferred inorganic pigments are metal oxides or hydroxides, such as, for example, titanium dioxide or ZnO as a white pigment, iron oxide (Fe2O3) as a red pigment, or iron hydroxide (FeOOH) as a yellow pigment. Preferred organic pigments are azo pigments, such as, for example, monoazo yellow and orange pigments, diazo pigments or β-naphthol pigments, and non-azo or polycyclic pigments, such as, for example, phthalocyanine, quinacridone, perylene and anthracene pigments. Azo pigments and non-azo pigments are particularly preferred.
[0131] In addition, the dental material according to the present invention may comprise one or more plasticizers. Plasticizers prevent polymers from becoming brittle after photochemical curing and possible drying. In addition, plasticizers ensure sufficient flexibility. Plasticizers are preferably added in a concentration of 0.2 to 5% by weight. Preferred plasticizers are phthalates, such as, for example, dibutyl phthalate or dihexyl phthalate, non-acidic phosphates, such as, for example, tributyl phosphate or tricresyl phosphate, n-octanol, glycerol or polyethylene glycol. Particularly preferred are tartrates or citrates, such as, for example, triester citrate, which are characterized by good biocompatibility.
[0132] The dental material according to the invention may further comprise one or more thixotropic additives. These additives lead to a thickening of the material and thus, for example, can prevent the filler from settling. In particular, the filler-containing material therefore preferably comprises at least one thixotropic additive. Preferred thixotropic additives are polymers containing OH groups, such as, for example, cellulose derivatives and inorganic substances, such as, for example, sheet silicates. In order not to increase the viscosity of the material excessively, the dental material according to the invention preferably comprises only 0 to 3.0% by weight, particularly preferably 0 to 2.0% by weight, very particularly preferably 0.1 to 2.0% by weight of thixotropic additives, relative to the total weight of the material.
[0133] Certain fillers, such as, for example, highly dispersed SiO2, i.e., having a small primary particle size (<20 nm) and a large surface area (>100 m 2 ) of SiO2, also has thixotropic effect. This filler can replace thixotropic additives.
[0134] The rheological properties of the dental material according to the invention are matched to the desired intended application. The materials for stereolithography methods are preferably adjusted so that their viscosity is in the range of 50 mPa·s to 100 Pa·s, preferably 100 mPa·s to 10 Pa·s, particularly preferably 100 mPa·s to 5 Pa·s. The viscosity is determined at 25° C. using a cone-plate viscometer (shear rate 100 / s). The dental material according to the invention particularly preferably has a viscosity of <10 Pa·s and very particularly preferably <5 Pa·s at 25° C. The viscosity is preferably measured rotationally using an Anton Paar MCR 302 viscometer with a CP25-2 cone-plate measuring system and a measuring gap of 53 μm at a shear rate of 100 / s. Due to the low viscosity, the dental material according to the invention is particularly suitable for processing using additive manufacturing methods such as, for example, 3D printing or stereolithography. The processing temperature is preferably in the range of 10 to 70° C., particularly preferably in the range of 20 to 30° C.
[0135] According to the invention, dental materials having the following composition are particularly preferred:
[0136] (a) 30 to 70% by weight, preferably 30 to 61% by weight, particularly preferably 40 to 60% by weight, of at least one aromatic, bicyclic or tricyclic mono(meth)acrylate,
[0137] (b) 20 to 60% by weight, preferably 30 to 55% by weight and particularly preferably 33 to 55% by weight of at least one urethane di(meth)acrylate telechelic having a number-average molar mass of 750 to 2000 g / mol,
[0138] (c) 0 to 30% by weight, preferably 0 to 20% by weight, and particularly preferably 0% by weight of a di(meth)acrylate monomer(s),
[0139] (d) 1 to 12% by weight, preferably 2 to 12% by weight, particularly preferably 2 to 10% by weight, of at least one ABA or AB block copolymer,
[0140] (e) 0.1 to 5.0% by weight, preferably 0.2 to 4.0% by weight and particularly preferably 0.3 to 3.0% by weight of at least one initiator for free-radical polymerization,
[0141] (f) 0 to 15% by weight, preferably 0 to 5% by weight and particularly preferably 0% by weight of core-shell polymer particles,
[0142] (g) 0 to 20% by weight, preferably 0 to 15% by weight and particularly preferably 0 to 10% by weight of fillers,
[0143] (h) 0 to 1.0% by weight, preferably 0 to 0.7% by weight and particularly preferably 0 to 0.5% by weight of UV absorbers,
[0144] (i) 0 to 0.5% by weight, preferably 0 to 0.1% by weight, and particularly preferably 0 to 0.05% by weight of a fluorescent whitening agent and
[0145] (j) 0 to 15% by weight, preferably 0 to 10% by weight, and particularly preferably 0.05 to 5% by weight of other additives.
[0146] Dental materials having the following composition are very particularly preferred:
[0147] (a) 30 to 70% by weight, preferably 30 to 61% by weight and particularly preferably 40 to 60% by weight of at least one mono(meth)acrylate of the formula (I),
[0148] (b) 20 to 60% by weight, preferably 30 to 55% by weight and particularly preferably 33 to 55% by weight of at least one urethane di[meth]acrylate telechelic compound of the formula (II),
[0149] (c) 0 to 30% by weight, preferably 0 to 20% by weight, and particularly preferably 0% by weight of other di(meth)acrylate monomers,
[0150] (d) 2 to 12% by weight, preferably 2 to 10% by weight and particularly preferably 3 to 8% by weight of at least one ABA or AB block copolymer,
[0151] (e) 0.1 to 5.0% by weight, preferably 0.2 to 4% by weight and particularly preferably 0.3 to 3.0% by weight of at least one photoinitiator,
[0152] (f) 0 to 15% by weight, preferably 0 to 5% by weight and particularly preferably 0% by weight of core-shell polymer particles,
[0153] (g) 0 to 20% by weight, preferably 0 to 15% by weight and particularly preferably 0 to 10% by weight of fillers,
[0154] (h) 0 to 1.0% by weight, preferably 0 to 0.7 and particularly preferably 0 to 0.5% by weight, of UV absorbers,
[0155] (i) 0 to 0.5% by weight, preferably 0 to 0.1% by weight, and particularly preferably 0 to 0.05% by weight of a fluorescent whitening agent and
[0156] (j) 0 to 15% by weight, preferably 0 to 10% by weight, and particularly preferably 0.02 to 5% by weight of other additives.
[0157] Unless otherwise stated, all weight percentages herein relate to the total mass of the dental material.
[0158] Particularly preferred according to the invention are dental materials comprising:
[0159] (a) 40 to 61% by weight of 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2[(benzyloxycarbonyl)amino]ethyl (meth)acrylate, 1-phenoxyprop-2-yl (meth)acrylate, 2-(benzyloxy)-ethyl (meth)acrylate, 2-(methacryloyloxy)ethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, phenoxypropyl (meth)acrylate, 2-benzyloxyethyl (meth)acrylate, 2-benzoyloxyethyl (meth)acrylate, methyl 2-(meth)acryloyloxybenzoate, 2-phenylethyl (meth)acrylate, tricyclodecyl (meth)acrylate, tricyclodecyl methyl (meth)acrylate and / or 2-(p-cumylphenoxy)ethyl methacrylate,
[0160] (b) 33 to 55% by weight of at least one urethane di(meth)acrylate telechelic having a number-average molar mass of 750 to 2000 g / mol and having at least 4 urethane groups, prepared by reacting 1 mol of ethoxylated or propoxylated bisphenol A, decanediol or dodecanediol with 2 mol of isophorone diisocyanate (IPDI) and subsequently with 2 mol of 2-hydroxyethyl methacrylate (HEMA) or hydroxypropyl methacrylate (HPMA),
[0161] (c) 0% by weight of other di(meth)acrylate monomers,
[0162] (d) 2 to 10 wt. % of at least one ABA or AB block copolymer, wherein the A blocks consist of oligomeric polycaprolactone, poly(2,6-dimethyl-1,4-phenylene oxide), poly(ethylene oxide), poly(propylene oxide) or poly(meth)acrylate structural units and the B blocks consist of poly(dimethylsiloxane), poly(isoprene), poly(vinyl acetate), poly(isobutylene), cis-poly(butadiene) or poly(ethylene) structural units,
[0163] (e) 0% core-shell polymer,
[0164] (f) 0.1 to 5.0 wt. % of at least one photoinitiator and
[0165] (g) 0.2 to 5% by weight of one or more other additives.
[0166] The dental materials according to the invention are characterized in that they have high fracture toughness and work of fracture measured in water at 37° C. and at the same time good flexural strength and a relatively high modulus of elasticity, which corresponds to oral conditions. The material also has high transparency and low viscosity. It is particularly advantageous that the dental material has high transparency and low intrinsic color even after curing.
[0167] In contrast, the core-shell polymers used as impact modifiers in the prior art generally bring about a more or less significant reduction in transparency, which is disadvantageous for additive methods. It was found that block copolymers (d) make it possible to improve fracture toughness, but only cause relatively small impairment of transparency compared to core-shell polymers. In addition, since much smaller amounts of block copolymers (d) are required to achieve the desired fracture toughness compared to core-shell polymers, block copolymers (d) make it possible to produce materials with high transparency, which is very suitable for additive methods.
[0168] When the crosslink density of the material c 300-5000mol / m 3 Range, preferably 400-3000 mol / m 3 The improvement of the fracture toughness of the block polymer (d) is particularly significant when the crosslinking density is within the range of 0.1% to 0.1%. Although a higher crosslinking density brings an increase in flexural strength and elastic modulus, it leads to a lower fracture strength of the polymer. A decrease in crosslinking density increases fracture toughness but has an adverse effect on flexural strength and elastic modulus.
[0169] A crosslinking density within the preferred range is achieved by using as crosslinking agent a urethane di(meth)acrylate telechelic compound (b) having a number average molar mass of 750-2000 g / mol, wherein the crosslinking density can be finely adjusted by adding small amounts of monomeric di(meth)acrylate.
[0170] According to the invention, materials with a transparency of ≥60%, preferably ≥70%, very particularly preferably ≥80%, and a viscosity of ≤10.0 Pa·s, preferably ≤5.0 Pa·s are particularly preferred. As mentioned above, the transparency is measured according to ISO 10526:1999. The viscosity is determined in the above-mentioned manner using a cone-plate viscometer.
[0171] After curing, the material according to the invention has a strength of more than 1.1 MPa·m 1 / 2 , preferably greater than 1.2MPa·m 1 / 2 , especially preferably greater than 1.4 MPa·m 1 / 2 Fracture toughness K max and greater than 250 J / m 2 , preferably greater than 300 J / m 2 , especially preferably greater than 400 J / m 2 Workpieces made of these materials can therefore undergo deformation to a large extent without breaking. The combination of high transparency and high work of rupture cannot be achieved using core-shell polymers.
[0172] Fracture toughness K max The determination of K and FW is carried out in a 3-point bending test according to ISO 20795-1:2013 with a support span of 32 mm. max and FW are determined based on the stress intensity factor K 1C Theoretical principle of fracture toughness K max is the maximum factor of stress intensity, also called the stress intensity factor at maximum load, and is calculated as follows:
[0173] MPa·m 1 / 2 ,in
[0174]
[0175] in
[0176] W is the specimen height (=8 mm), B is the specimen thickness (=4 mm), a is the crack length (=3 mm + blade crack depth), S is the support span (=32 mm) and P max is the maximum pressure in the test.
[0177] The fracture work FW (fracture work, total fracture work) is calculated as follows:
[0178]
[0179] Where U is the total energy required to fracture the sample (integral of the load / distance diagram) and is the total energy required to create two new fracture planes B(Wa). This parameter describes the material's resistance to crack growth.
[0180] After curing, the material according to the present invention has good flexural strength and relatively good flexural modulus as well as good fracture toughness and high work of fracture. The molded parts obtained by curing the material according to the present invention have high rigidity and resist deformation with a high level of impedance without breaking. Materials having a flexural strength of at least 40 MPa, particularly preferably 50 MPa or higher, very particularly preferably 60 MPa or higher, measured according to ISO 20795-1: 2013 after curing are preferred. In addition, the cured material preferably has a flexural modulus of at least 1000 MPa, preferably 1300 MPa or higher, particularly preferably 1500 MPa or higher, very particularly preferably 2000 MPa or higher and most preferably 2500 MPa, measured according to ISO 20795-1: 2013. In addition, the fracture toughness K of the material is max 1.1MPa·m 1 / 2 or greater, preferably 1.2 MPa·m 1 / 2 or greater, particularly preferably 1.4 MPa·m 1 / 2 or greater, and the work of fracture FW is 250 J / m 2 or greater, preferably 300 J / m 2 or more, particularly preferably 400 J / m 2 Therefore, the bending strength of the material is 60 to 100 MPa, the bending modulus is 2000 to 2500 MPa, and the fracture toughness K max 1.4 to 2.5 MPa·m 1 / 2 , the fracture work FW is 400 to 800 J / m 2 It is particularly preferred.
[0181] According to a particularly preferred embodiment of the present invention, after curing, the material has a flexural strength of 50 MPa or more measured according to ISO 20795-1:2013 and a thermal conductivity of 250 J / m 2 or higher fracture work and at least 1.2 MPa·m 0.5 K max value (highest factor of stress intensity).
[0182] Due to the above-mentioned properties, the material according to the invention is very suitable for use as a dental material, for example as a prosthetic material or facing material, in particular for the production or repair of dental molded parts, such as, for example, dental restorations, prostheses, dentures, inlays, onlays, crowns, bridges, drilling templates, splints (bite splints), trial fittings and orthodontic appliances, such as, for example, plastic corrective splints, so-called orthodontic appliances and positioners. The specified molded parts are also the subject of the present invention. The dental material according to the invention is preferably used extraorally, i.e. non-therapeutic.
[0183] Another subject of the present invention is a method for producing a dental molded part, in particular a method for producing a dental molded part as described above, wherein the composition according to the invention is cured with the aid of light to give a dental molded part. The production or restoration of the dental molded part is preferably carried out extraorally, particularly preferably by an additive process, very particularly preferably by 3D printing or a lithography-based process, such as, for example, stereolithography.
[0184] The stereolithographic production of the molded part is preferably carried out by directly or indirectly digitizing one or more teeth to be restored on a computer to create a virtual image of the dental condition, then building a model of the dental restoration or prosthesis on the computer based on the image, and subsequently preparing and manufacturing the model by additive stereolithography.
[0185] Once a virtual model of the dental workpiece to be manufactured has been created, the composition according to the invention is polymerized by selective light irradiation. The dental restoration or prosthesis is preferably constructed in layers by polymerizing a plurality of thin layers with the desired cross-section one after another. After the layered construction of the restoration or prosthesis, the excess residual resin is preferably removed. This can be carried out by suitable mechanical methods (e.g. centrifugation or sandblasting) or by treatment with a suitable solvent such as, for example, an alcohol, such as ethanol or isopropanol, a ketone such as, for example, acetone, or an ester such as, for example, ethyl acetate. Post-tempering is then preferably carried out by heating or particularly preferably by irradiating the workpiece with light of a suitable wavelength, such as, for example, at 405 nm with an intensity of, for example, 160 mW / cm 2 When two photoinitiators are used, it is advantageous to irradiate with two different wavelengths. Preferably, the workpiece is heated to a temperature above 50° C. simultaneously or in a subsequent step. The mechanical properties can be improved by photochemical and / or thermal post-tempering. DETAILED DESCRIPTION
[0186] The present invention is explained in more detail below with reference to Examples.
[0187] Example
[0188] Example 1
[0189] Synthesis of 2-(2-biphenyloxy)-ethyl methacrylate (aromatic monomethacrylate)
[0190] Phase 1: 2-(2-biphenyl)-oxyethanol
[0191]
[0192] In a double-jacketed reactor, 2.55 kg (15.0 mol) of 2-phenylphenol, 0.12 kg (0.75 mol) of potassium iodide and 0.17 kg (0.75 mol) of benzyltriethylammonium chloride are added to a solution of 0.90 kg (22.5 mol) of sodium hydroxide in 15.0 kg of water. The solution is heated to 60° C. (internal temperature) and the dropwise addition of 1.81 kg (22.5 mol) of 2-chloroethanol is simultaneously started. After the addition is complete, the batch is stirred at 60° C. for 48 hours. For workup, the batch is diluted with 6.0 liters of toluene and, after phase separation, the aqueous phase is extracted twice more with 3.0 liters of toluene each time. The combined toluene phases are washed 3 times with 4.0 liters of 1N sodium hydroxide solution each time, 3 times with 4.0 liters of 1N hydrochloric acid each time and 3 times with 3.0 liters of water each time. The toluene is distilled off in vacuo. After recrystallization from toluene, 2.77 kg (86% yield) of 2-(2-biphenyl)-oxyethanol were obtained as a colorless crystalline solid (mp: 74-75° C.) with a purity of >99% (GC).
[0193] 1 H-NMR (400MHz, CDCl3) δ (ppm) = 1.86 (t, J = 6.5Hz, 1H, OH), 3.78-3.81 (m, 2H, HOCH2), 4.04 (t, J=4.6Hz, 2H, OCH2), 6.98-7.08, 7.28-7.34, 7.38-7.42 and 7.50-7.52 (4m, 2H, 3H, 2H, 2H, =CH).
[0194] 13 C-NMR (100 MHz, CDCl3) δ (ppm) = 61.4 and 70.3 (OCH2), 113.5 (C-6), 121.7 (C-4), 127.1, 128.7 and 131.0 (C-3, C-5, C-4'), 128.1 and 129.4 (C-2', C-3', C-5', C-6'), 131.5 and 138.4 (C-2, C-1'), 155.4 (C-1).
[0195] IR(diamond ATR):ν(cm -1)=3329(br,m,OH),3056(m,=CH),2918 and 2866(m,CH2),1596 and 1584(m,C=C),1502 and 1483(s,aromatic compounds),1431(s,CH2),1260 and 1077(s,COC),1054(s,COH),749,730 and 700(vs,=CH).
[0196] Second stage: 2-(2-biphenyloxy)-ethyl methacrylate
[0197]
[0198] In a double jacket reactor, 0.75 kg (7.4 mol) of triethylamine, 37.9 g (0.31 mol) of 4-dimethylaminopyridine and 0.35 g of 2,6-di-tert-butyl-4-methylphenol were added to a solution of 1.33 kg (6.2 mol) of 2-(2-biphenyl)-oxyethanol in 13.0 liters of dichloromethane. 1.14 kg (7.4 mol) of methacrylic anhydride solution was added dropwise at 0° C. (internal temperature) and stirred for a further 2 hours at this temperature and for 20 hours at 20° C. The solution was then washed 3 times with 4.0 liters of 1N hydrochloric acid, 3 times with 4.0 liters of 1N sodium hydroxide solution and 3 times with 4.0 liters of water. The organic phase was stabilized with 0.09 g of phenothiazine. After removal of the solvent, 1.71 kg (98% yield) of 2-(2-biphenyloxy)-ethyl methacrylate (BPOEMA) was obtained as an almost colorless oil with a purity of 96.45% (GC).
[0199] 1 H-NMR (400 MHz, CDCl3) δ (ppm) = 1.93 (s, 3H, CH3), 4.19 and 4.41 (2t, each J = 4.8 Hz, each 2H, OCH2), 5.55 and 6.08 (2s, each 1H, = CH2), 6.95-7.06, 7.26-7.30, 7.33-7.37 and 7.52-7.55 (4m, 2H, 2H, 3H, 2H, = CH).
[0200] 13C-NMR (100 MHz, CDCl3) δ (ppm) = 18.3 (CH3), 63.0 and 66.5 (OCH2), 113.1 (C-6), 121.7 (C-4), 126.0 (C=CH2), 126.9, 128.6, 131.1 (C-3, C-5, C-4'), 127.9 and 129.6 (C-2', C-3', C-5', C-6'), 131.3 and 138.3 (C-2, C-1'), 136.1 (C=CH2), 155.4 (C-1), 167.2 (C=O).
[0201] IR(diamond ATR):ν(cm -1 )=3027(w,=CH),2955 and 2900(w,CH2,CH3),1716(vs,C=O),1636(m,C=C 甲基丙烯酰基 ), 1598 and 1584 (m, C = C 芳族化合物 ), 1504 and 1482 (m, s, aromatic compounds), 1434 (s, CH2, CH3), 1261 and 1125 (s, COC 醚 ),1157(vs,COC 酯 ),939(s,=CH 甲基丙烯酰基 ),751,733 and 697 (vs, = CH 芳族化合物 ).
[0202] The rotational viscosity of BPOEMA was measured using an MCR rheometer (Anton Paar GmbH, Austria) and was η=0.01 Pa·s. The refractive index of BPOEMA was measured using an ABBE 5 refractometer (Bellingham+Stanley, UK) and was n D 20 =1.5729. The density of BPOEMA was determined by means of a bending resonator densitometer DS 7000 (Krüss) and was 1.119 g / cm 3 The polymerization shrinkage of the monomer was measured to be only 7.4% by volume.
[0203] Example 2
[0204] Synthesis of urethane dimethacrylate telechelic compound according to the present invention
[0205] General guidelines for reacting diols with diisocyanates and HEMA end-capping (1:2:2)
[0206] A mixture of 1 equivalent of diol, 2 equivalents of isophorone diisocyanate (IPDI) and 700 ppm of Metatin 712 (relative to IPDI) is heated to 40°C. The diol is completely dissolved and the mixture is heated to about 110°C. After the exotherm has subsided, the mixture is stirred at 80°C bath temperature for 1 hour and then 2 equivalents of 2-hydroxyethyl methacrylate (HEMA, stabilized with 30 ppm (relative to 100% product) BHT are added dropwise. After the exotherm has subsided again, stirring is continued at 90°C for another 10 minutes. The completeness of the reaction is checked by IR and NMR spectroscopy. The adduct obtained is a colorless, very highly viscous to brittle resin.
[0207] A. 1,10-Decanediol-IPDI-HEMA adduct (1:2:2), isomer mixture (DMA telechelic 1, molar mass: 879.15 g / mol)
[0208]
[0209] 1,10-Decanediol was used as diol.
[0210] 1 H NMR (400 MHz, CDCl3): δ (ppm) = 0.85-0.97, 1.01-1.06, 1.19-1.38 and 1.59-1.75 [4m, 46H, (CH2)8, CH 2,环. ,CH 3,环. ),2.03(s,6H,CH 3,甲基丙烯酰基 ),2.81-2.98 and 3.20-3.33(2m,4H,NCH2),3.65-3.88[m,2H,NCH],3.98-4.11(m,4H,OC H 2(CH2)8), 4.26-4.40 (m, 8H, O(CH2)2O), 4.57-4.94 (m, 4H, NH), 5.60 and 6.14 (2s, each 2H,=CH2).
[0211] IR(diamond ATR):ν(cm -1 )=3341(br,NH),2927 and 2856(m,CH),1695(vs,C=O),1638(m,C=C),1526(s,NH),1456(m,CH2,CH3),1366(m,CH3),1236(CN),1167 and 1039(s,m,COC),942(m,=CH),774[m,(CH2)8].
[0212] B. Bisphenol A-IPDI-HEMA adduct (1:2:2), isomer mixture (DMA telechelic 2, molar mass: 1049.31 g / mol)
[0213]
[0214] Bisphenol A derivatives having pendant isopropoxy groups according to the following formula are used as diols:
[0215]
[0216] 1 H NMR (400MHz, CDCl3): δ (ppm) = 0.86-1.06, 1.18-1.21, 1.29-1.40 and 1.62-1.75 [4 m, 42H, CH 2,环 ,CH3),1.95(s,6H,CH 3,甲基丙烯酰基 ), 2.87-2.99 and 3.19-3.36 (2 m, 4H, NCH2), 3.67-3.88 [m, 2H, NCH], 3.91-4.03 and 4.09-4.22 (2 m, 4H, OC H 2CH), 4.26-4.40 and 4.50-5.18 (2m, 14H, O(CH2)2O, OCH2C H , NH), 5.59 and 6.15 (2 s, each 2H, =CH2), 6.80 and 7.12 (2 d, each 4H, =CH).
[0217] IR(diamond ATR):ν(cm -1 )=3341(br,NH),2955 and 2860(m,CH),1705(vs,C=O),1640(w,C=C),1608(w,aromatic compounds),1507(s,NH),1456(m,CH2,CH3),1385(m,CH3),1231(CN),1155 and 1043(s,m,COC),941(m,=CH),829(m,=CH 芳族化合物 ).
[0218] Example 3
[0219] Synthesis of PCL(1600)-b-PDMS(3200)-b-PCL(1600) Block Copolymer (PO-277)
[0220] Stage 1: 3-Aminopropyldimethylsilanoltetramethylammonium
[0221] A mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (2.49 g, 10.0 mmol) and tetramethylammonium hydroxide pentahydrate (3.62 g, 20 mmol) in tetrahydrofuran (THF; 10 ml) was heated to reflux for 3 hours under protective gas. The solvent was evaporated and the residue was heated to 50° C. in a high vacuum. The pale yellow residue was recrystallized from THF (20 ml). 3.17 g (15.4 mmol; 77%) of a white solid were obtained.
[0222] 1 H-NMR (CDCl3, 400 MHz): δ = 3.16 (s, 12H; N + -CH3), 2.37 (t, 2H; J=7.1Hz; N-CH2), 1.28 (m, 2H; CH2), 0.14 (m, 2H; Si-CH2), -0.33 (s, 6H; Si-CH3).
[0223] Second stage: Polydimethylsiloxane-αω-dipropyl-3-amine: PDMS (3200)
[0224] In a protective gas atmosphere, a mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (4.98 g, 20.0 mmol) and octamethylcyclotetrasiloxane (12.00 g, 40 mmol) was heated to 80 ° C. 3-aminopropyldimethylsilanol tetramethylammonium (20 mg) was added and stirring was continued at 80 ° C. After 30 minutes, octamethylcyclotetrasiloxane (56.00 g, 0.192 mol) saturated with argon was slowly added dropwise. The reaction mixture was stirred at 80 ° C for another 18 hours and then heated to 150 ° C for 30 minutes to decompose the catalyst. The volatile components were then removed in a high vacuum. 65.30 g (88%) of colorless oil were obtained.
[0225] 1 H-NMR (CDCl3, 400 MHz): δ = 2.64 (t, 4H; J = 7.0 Hz; N-CH2), 1.43 (m, 4H; CH2), 0.51 (m, 4H; Si-CH2), 0.05 (s, 250H; Si-CH3).
[0226] The third stage: PCL (1600) -b-PDMS (3200) -b-PCL (1600) block copolymer
[0227] A mixture of PDMS (3200) (20.00 g) and ε-caprolactone (20.40 g) was heated to 80° C. After 1 hour, bis(2-ethylhexanoate)tin (10 mg) was added and the bath temperature was raised in stages to 130° C. over 30 minutes. The now clear reaction mixture was stirred at 130° C. for a further 5 hours. The volatile components were then distilled off in a high vacuum. 39.50 g (98%) of the block copolymer were obtained as a waxy, pale yellow solid.
[0228] 1 H-NMR (CDCl3, 400 MHz): δ = 3.99 (t, 55H; J = 6.8 Hz; O-CH2), 3.57 (t, 4H; J = 6.8Hz; HO-CH2), 3.15 (q, 4H; J = 6.8 Hz; N-CH2), 2.24 (t, 55H; J = 7.5Hz; C(O)-CH2), 2.10 (t, 4H; J = 7.5 Hz; N-CH2), 1.58 (m, 118H; CH2), 1.32 (m, 59H; CH2), 0.46 (m, 4H; Si-CH2), 0.02 (s, 250H; Si-CH3).
[0229] Example 4
[0230] Synthesis of PMMA(1200)-b-PDMS(3200)-b-PMMA(1200) Block Copolymer
[0231] Phase 1: α, -(2-Bromoisobutyrylaminopropyl)-poly(dimethylsiloxane)
[0232] β-Bromoisobutyric acid bromide (1.44 g; 6.24 mmol) is added dropwise to a solution of PDMS (3200) (6.66 g; 2.08 mmol) and triethylamine (0.84 g; 8.44 mmol) dissolved in THF (100 ml) at 0°C. The reaction mixture is stirred for 2 hours under ice cooling and for 18 hours at ambient temperature. The suspension is filtered and the filtrate is concentrated on a rotary evaporator. The colorless oil is dissolved in dichloromethane (100 ml), washed with saturated aqueous Na2CO3 solution (2 times 50 ml), hydrochloric acid (0.2N, 2 times 50 ml) and saturated aqueous NaCl solution (100 ml), dried over anhydrous sodium sulfate, filtered and concentrated on a rotary evaporator. The volatile components are removed in a high vacuum. 6.32 g (1.81 mmol; 87%) of a pale yellow liquid are obtained.
[0233] 1H-NMR (CDCl3, 400 MHz): δ = 3.22 (m, 4H; N-CH2), 1.92 (s, 12H; C-CH3), 1.54 (m, 4H; CH2), 0.53 (m, 4H; Si-CH2), 0.05 (s, 258H; Si-CH3).
[0234] Second stage: PMMA (1200)-b-PDMS (3200)-b-PMMA (1200) block copolymer
[0235] Under inert gas conditions, toluene (50 ml) was added to α, -(2-bromoisobutyramidopropyl)-poly(dimethylsiloxane) (6.22 g; 1.78 mmol), cuprous (I) chloride (0.35 g; 3.56 mmol) and N,N,N',N",N"-pentamethyldiethylenetriamine (0.62 g; 3.56 mmol) were added and the solution was degassed. Methyl methacrylate (7.78 g; 77.7 mmol) was added. The solution was stirred at ambient temperature for 30 minutes and then heated to 90°C for 20 hours. After cooling, the solution was filtered over neutral alumina. The filtrate was concentrated on a rotary evaporator. The residue was dissolved in dichloromethane and filtered through silica gel. The filtrate was concentrated on a rotary evaporator and the residue was dried in a high vacuum. 8.77 g (1.49 mmol; 84%) of the block copolymer were obtained as a light yellow solid.
[0236] 1 H-NMR (CDCl3, 400 MHz): δ = 3.53 (s, 72H; O-CH3), 3.28–3.03 (m, 4H; N-CH2), 2.20–1.12 (m, 64H; C-CH3, CH2), 1.13–0.63 (m 72H,CH3),0.55–0.40(m,4H;Si-CH2),0.0(s,252H,Si-CH3).
[0237] Example 5
[0238] Synthesis of PCL(2500)-b-PDMS(3200)-b-PCL(2500) Block Copolymer
[0239] A mixture of PDMS (3200) (20.00 g) and ε-caprolactone (30.60 g) was heated to 80° C. After 1 hour, bis(2-ethylhexanoate)tin (10 mg) was added and the bath temperature was raised in stages to 130° C. over 30 minutes. The now clear reaction mixture was stirred at 130° C. for a further 5 hours. The volatile components were then distilled off in a high vacuum. 49.00 g (97%) of a waxy, pale yellow solid were obtained.
[0240] 1H-NMR (CDCl3, 400MHz): δ = 3.99 (t, 86H; J = 6.8Hz; O-CH2), 3.57 (t, 4H; J = 6.8Hz; HO-CH2), 3.15 (q, 4H; J = 6.8Hz; N-CH2), 2.24 (t, 86H; J = 7.5Hz; C (O)-CH2), 2.10 (t, 4H; J=7.5Hz; N-CH2), 1.60-1.54 (m, 180H; CH2), 1.34-1.29 (m, 90H; CH2), 0.51-0.40 (m, 4H; Si-CH2), 0.02 (s, 250H; Si-CH3).
[0241] Example 6
[0242] Synthesis of PCL(3200)-b-PDMS(3200)-b-PCL(3200) Block Copolymer
[0243] A mixture of PDMS (3200) (15.00 g) and ε-caprolactone (30.60 g) was heated to 80° C. After 1 hour, tin bis(2-ethylhexanoate) (10 mg) was added and the bath temperature was raised in stages to 130° C. over 30 minutes. The now clear reaction mixture was stirred at 130° C. for a further 5 hours. The volatile components were then distilled off in a high vacuum. 44.20 g (97%) of a waxy, pale yellow solid were obtained.
[0244] 1 H-NMR (CDCl3, 400MHz): δ = 3.99 (t, 106H; J = 6.8Hz; O-CH2), 3.57 (t, 4H; J = 6.8Hz; HO-CH2), 3.15 (q, 4H; J = 6.8Hz; N-CH2), 2.24 (t, 106H; J = 7.5Hz; C (O)-CH2), 2.10 (t, 4H; J=7.5Hz; N-CH2), 1.60-1.54 (m, 220H; CH2), 1.34-1.29 (m, 110H; CH2), 0.51-0.40 (m, 4H; Si-CH2), 0.02 (s, 250H; Si-CH3).
[0245] Example 7
[0246] Polymerization and preparation of SL resin
[0247] The components listed in Table 1 are mixed uniformly with each other in the specified amounts. To this end, all solid components (block copolymers or core-shell particles, photoinitiators) are dissolved in the monomers under stirring in a planetary mixer or a speed mixer (Speedmixer), optionally also heated to 50° C. The urethane dimethacrylate telechelic compound is then added and stirring is continued until a homogeneous mixture is obtained. The block copolymer can be incorporated into the mixture without any problems. In order to incorporate the core-shell particles, homogenization is additionally carried out for 30 minutes at a rotation speed of 3000 rpm by means of a rotor-stator mixer (Ultra-Turrax T-25). The mixture is then degassed in a planetary mixer.
[0248] The test pieces were produced in a bottom-up process using a stereolithography printer (PrograPrint PR5 from Ivoclar Vivadent AG, Schaan, Liechtenstein) with recipes No. 5 and No. 6. The printer used DLP technology with a wavelength of 388 nm, 10 mW / cm 2 The samples were exposed in a layered construction with a power of 100 μm and a pixel size of 50 μm. In each case, the layer thickness was 100 μm. Isopropanol was used to remove the adhering residual resin. To this end, the specimen was cleaned twice with fresh isopropanol under stirring together with the build platform (PrograPrint Stage) using the PrograPrint Clean device (from Ivoclar Vivadent AG, Schaan, Liechtenstein) (10 minutes in the first bath and 5 minutes in the second bath) and then immediately blown dry with compressed air. Then, post-tempering was performed by exposing the specimen to light with a wavelength of 405 nm for 90 seconds. This was achieved with the aid of the PrograPrint Cure device (from Ivoclar Vivadent AG, Schaan, Liechtenstein; software: ProArt Print Splint, 2020). The specimen was then removed from the build platform.
[0249] Test pieces were produced in a metal mold with the remaining composition from Table 1 and irradiated on both sides with a dental light source (PrograPrintCure from Ivoclar Vivadent AG, Schaan, Liechtenstein; software: ProArt Print Splint, 2020) and thus cured.
[0250] Further processing and storage of the test pieces were carried out in accordance with the relevant provisions of the specifications specified below. The flexural strength (FS) and the flexural modulus of elasticity (FM) were determined in accordance with ISO standard ISO-4049 (Dentistry – Polymer-based filling, restorative and sealing materials). For this purpose, the test pieces were previously stored dry at room temperature for 24 h or in water at 37 °C for 24 h. In addition, the flexural strength and flexural modulus were measured in accordance with ISO 20795-1:2013 standard (Dentistry – Base polymers – Part 1: Denture base polymers). Therefore, before the measurement, the test pieces were stored in deionized water at 37 °C for 50 h and then measured under water at 37 °C in a thermostatically controlled tank. Fracture toughness K max The determination of the strength and the work of fracture FW was carried out according to ISO 20795-1: 2013. The measurement results are given in Table 2.
[0251] Formulations No. 1 and No. 10 are reference examples, which contain neither core-shell polymer nor block copolymer. Although these reference examples have good flexural strength and good flexural modulus, the values of fracture toughness and fracture work are poor and cannot be used for the intended stereolithography applications. Examples No. 3, No. 4 and No. 14 each contain core-shell polymer particles. In all cases, the addition of particles leads to improved fracture toughness (K max and fracture work FW).
[0252] In Example No. 14, 5 wt % of core-shell particles are added to Formula No. 10. The addition of core-shell polymer not only brings about an improvement in fracture toughness, but also a significant deterioration in transparency. In Example Nos. 12, 13 and 15, in each case, 5 wt % of block copolymer is added as an impact modifier instead of core-shell particles. Table 2 shows that in all cases, the improvement in fracture toughness of block copolymers is much greater than that of core-shell particles, but only causes a relatively small deterioration in transparency. Example No. 11 shows that the addition of 3 wt % of block copolymer is sufficient to achieve an improvement in fracture toughness similar to 5 wt % core-shell particles.
[0253] Comparison of Example No. 2 and No. 3 shows that here too, the addition of 3 wt. % block copolymer improves fracture toughness in a manner similar to that of 5 wt. % core-shell particles. Compared to Example No. 3, Example No. 2 is characterized by a higher transparency and confirms that the use of block copolymers makes it possible to produce materials with high fracture toughness and transparency.
[0254] Comparison of Example No. 3 and No. 4 shows that, although fracture toughness can be further improved by increasing the amount of core-shell particles from 5 wt % to 10 wt %, this is associated with an increased deterioration in transparency.
[0255] Table 1: Composition of polymer and SL resins (data in wt %)
[0256]
[0257] *) Comparative Example
[0258] a) Addition product of a mixture of 0.7 mol of 2-hydroxyethyl methacrylate and 0.3 mol of 2-hydroxypropyl methacrylate and 1 mol of α,α,α`,α`-tetramethyl-xylylene diisocyanate
[0259] b) 2-Phenoxyethyl methacrylate
[0260] c) Tricyclodecane methyl acrylate
[0261] d) Diphenyl (2,4,6-trimethylbenzoyl) phenyl phosphine oxide (BASF)
[0262] e) Core-shell polymer particles MZ110 (Kaneka)
[0263] f) PCL-b-PDMS-b-PCL block copolymer, the molar mass of the PDMS block is 3200 g / mol, and the molar mass of the PCL block is 1600 g / mol
[0264] Table 2: Properties of cured materials
[0265]
[0266] *) Comparative Example
[0267] nd Not determined
[0268] 1) Rotational viscosity, measured at 25°C with a shear rate of 100 / s using an Anton Paar MCR302 viscometer with a CP25-2 cone-plate measuring system and a 53 μm measuring gap
[0269] 2) Measured by transmittance (D65) on a 1 mm thick specimen polished to a high gloss using a Konika-Minolta CM-5 spectrophotometer
[0270] 3) The storage modulus and loss modulus of the test piece (25×5×1 mm, longitudinally clamped) were measured between 25°C and 250°C using an Anton Paar MCR 302 rheometer (frequency 1 Hz, deformation 0.05%, heating rate 2 K / min); T G Corresponds to the maximum loss factor tanδ (ratio of loss modulus to storage modulus)
[0271] 4) According to the formula ν c=G' / (RT) to calculate the network density, G' is the temperature T G Storage modulus at +50K; R is the universal gas constant; T is T G Temperature at +50K
[0272] 5) Flexural strength (FS) and flexural modulus (FM) measured in accordance with ISO4049 after dry storage at room temperature for 24 hours
[0273] 6) Flexural strength (FS) and flexural modulus (FM) measured in accordance with ISO4049 after storage in water at 37°C for 24 hours
[0274] 7) Flexural strength (FS) and flexural modulus (FM) measured according to ISO 20795-2.
Claims
1. A free radical polymerizable dental material comprising at least one ABA or AB block copolymer (d), at least one monofunctional, free-radically polymerizable monomer (a), optionally other free-radically polymerizable monomers (c), and at least one free-radically polymerizable urethane di(meth)acrylate telechelic compound (b) according to the general formula (II) having a number-average molar mass of 750 to 2000 g / mol, Formula II where the variables have the following meanings: R 1 , R 2 is in each case independently of one another H or methyl, R 3 , R 4 is in each case independently of one another H or methyl, x, y are in each case independently of one another an integer from 1 to 11, n is 1, 2, or 3, Z is DA is a structural element derived from a diol HO-DA-OH by cleaving a hydrogen atom from a hydroxyl group, wherein the diol HO-DA-OH is selected from the following compounds: ethoxylated or propoxylated bisphenol A, o- or p-diphenyl with 2 to 6 ethoxy or propoxy groups, C2-C 18 Alkanediols, cyclic or polycyclic aliphatic diols, in, The mixture of one or more A blocks and components (a) to (c) is homogeneously miscible, and the mixture of the B blocks and components (a) to (c) is inhomogeneously miscible.
2. The free radical polymerizable dental material according to claim 1, wherein The ethoxylated or propoxylated bisphenol A is selected from ethoxylated or propoxylated bisphenol A having 2, 3 or 4 ethoxy or propoxy groups.
3. The free radical polymerizable dental material according to claim 1, wherein The cyclic or polycyclic aliphatic diol is selected from cyclohexanediol, norbornanediol, tricyclodecanediol and tricyclodecane dimethanol.
4. The free radical polymerizable dental material according to claim 1, wherein The C2-C3-H2O2 ... 18 The alkanediol is selected from hexane-1,6-diol, octane-1,8-diol, nonane-1,9-diol, decane-1,10-diol, undecanediol or dodecane-1,12-diol, tetraethylene glycol or pentaethylene glycol.
5. A free-radically polymerizable dental material according to any one of claims 1 to 4, comprising, in each case relative to the total mass of the material (a) 30 to 70% by weight of at least one aromatic, bicyclic or tricyclic mono(meth)acrylate, (b) 20 to 60% by weight of at least one urethane di(meth)acrylate telechelic compound having a number-average molar mass of 750 to 2000 g / mol, (c) 0 to 30 wt % of di(meth)acrylate monomer(s), (d) 1 to 12 wt. % of at least one ABA and / or AB block copolymer, and (e) 0.1 to 5.0% by weight of at least one initiator for free radical polymerization.
6. A free-radically polymerizable dental material according to any one of claims 1 to 4, comprising as component (a) at least one aromatic, bicyclic or tricyclic monomethacrylate of the formula (I) Formula I where the variables have the following meanings: A is an aromatic group having 6 to 15 carbon atoms or a bicyclic or tricyclic aliphatic group having 7 to 10 carbon atoms, wherein A is unsubstituted or substituted by one or more C1-C5 alkyl groups, C1-C5 alkoxy groups and / or chlorine atoms; R is hydrogen or methyl; X 1 , X 2 is in each case independently of one another absent or an ether, ester or urethane group, wherein if Y 1 If it does not exist, then X 1 does not exist, and if Y 2 If it does not exist, then X 2 does not exist; Y 1 , Y 2 In each case independently of one another is absent or is a branched or straight-chain aliphatic hydrocarbon radical having 1 to 10 carbon atoms which is uninterrupted or interrupted by 1 to 3 oxygen atoms.
7. The free radical polymerizable dental material according to claim 6, comprising as component (a) 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, phenethyl (meth)acrylate, 2-[(benzyloxycarbonyl)-amino]-ethyl (meth)acrylate, 2-[(benzylcarbamoyl)-oxy]-ethyl (meth)acrylate, 1-phenoxyprop-2-yl (meth)acrylate and 2-(p-cumylphenoxy)ethyl (meth)acrylate, (meth)acrylate) ) 2-(benzyloxy)ethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, phenoxypropyl (meth)acrylate, 2-benzyloxyethyl (meth)acrylate, 2-benzoyloxyethyl (meth)acrylate, methyl 2-(meth)acryloyloxybenzoate, tricyclodecyl (meth)acrylate, tricyclodecyl methyl (meth)acrylate, 2-(p-cumylphenoxy)ethyl (meth)acrylate, 4,7,7-trimethylbicyclo[2.2.1]heptyl (meth)acrylate, octahydro-1H-4,7-methyleneinden-5-yl (meth)acrylate, or a mixture thereof.
8. A free-radically polymerizable dental material according to claim 5, comprising as component (d) at least one ABA and / or AB block copolymer, wherein the A block is an oligomer composed of one or more of the following monomers: cyclic, aliphatic esters or ethers, arylene oxides, alkylene oxides, free-radically polymerizable monomers, α,β-unsaturated acids and α,β-unsaturated acid esters; and the B block is a polysiloxane oligomer and / or a polyvinyl oligomer and / or a polyolefin oligomer and / or a polydiene oligomer.
9. A free-radically polymerizable dental material according to claim 8, comprising as component (d) at least one ABA and / or AB block copolymer, wherein the A blocks are oligomeric polycaprolactone (PCL), poly(2,6-dimethyl-1,4-phenylene oxide), poly(ethylene oxide), poly(propylene oxide) or poly(meth)acrylate structural units, and the B blocks are oligomeric poly(dimethylsiloxane) (PDMS), poly(isoprene), poly(vinyl acetate), poly(isobutylene), cis-poly(butadiene) or poly(ethylene) structural units.
10. A free-radically polymerizable dental material according to claim 9, comprising as component (d) at least one ABA triblock copolymer of the PCL-b-PDMS-b-PCL and / or PMMA-b-PDMS-b-PMMA type, whose A:B molar ratio is from 0.1 to 5 and whose molar mass is from 3 to 25 kDa, from 4 to 20 kDa or from 5 to 10 kDa.
11. A free-radically polymerizable dental material according to claim 5, comprising as component (e) at least one photoinitiator selected from benzophenone, benzoin or its derivatives, α-diketone or its derivatives, 9,10-phenanthrenequinone, 1-phenyl-propane-1,2-dione, diacetyl or 4,4'-dichlorobenzil, camphorquinone (CQ), 2,2-dimethoxy-2-phenylacetophenone or a combination of α-diketone and amine 4-(dimethylamino)-benzoate (EDMAB), N,N-dimethylaminoethyl methacrylate, N,N-dimethyl-sym-xylidine or triethanolamine as a reducing agent, monoacyltrialkylgermanium, diacyldialkylgermanium, tetraacylgermanium, tetraacylstannane, benzoyltrimethylgermanium, dibenzoyldiethylgermanium, bis(4-methoxybenzoyl)diethylgermanium, tetra(2-methylbenzoyl)germane or tetra( stannane or a mixture thereof, Norrish I type photoinitiators, which include acetophenone, 2,2-diethoxy-1-acetophenone, benzoin ethers, Irgacure 651 (benzil dimethyl ketal), hydroxyalkylphenyl acetophenone, Irgacure 184 (1-hydroxycyclohexyl phenyl ketone), acyl or bisacylphosphine oxides, Irgacure TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide), Irgacure 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide), 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone (Irgacure 369) and / or 1-butanone-2-(dimethylamino)-2-(4-methylphenyl)methyl-1-4-(4-morpholino)phenyl (Irgacure 379).
12. A free-radically polymerizable dental material according to any one of claims 1 to 4, having the following composition, in each case relative to the total mass of the material: (a) 30 to 70% by weight of at least one aromatic, bicyclic or tricyclic mono(meth)acrylate, (b) 20 to 60% by weight of at least one urethane di(meth)acrylate telechelic compound having a number-average molar mass of 750 to 2000 g / mol, (c) 0 to 30 wt % of di(meth)acrylate monomer(s), (d) 1 to 12% by weight of at least one ABA or AB block copolymer, (e) 0.1 to 5.0% by weight of at least one initiator for free-radical polymerization, (f) 0 to 15 wt. % core-shell polymer particles, (g) 0 to 20% by weight of fillers, (h) 0 to 1.0 wt. % of a UV absorber, (i) 0 to 0.5 wt. % of a fluorescent whitening agent and (j) 0 to 15% by weight of other additives.
13. The dental material according to claim 12, wherein (a) 40 to 61% by weight of 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-[(benzyloxycarbonyl)amino]ethyl (meth)acrylate, 1-phenoxyprop-2-yl (meth)acrylate, 2-(benzyloxy)-ethyl (meth)acrylate, 2-(methacryloyloxy)ethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, phenoxypropyl (meth)acrylate, 2-benzyloxyethyl (meth)acrylate, 2-benzoyloxyethyl (meth)acrylate, methyl 2-(meth)acryloyloxybenzoate, 2-phenylethyl (meth)acrylate, tricyclodecyl (meth)acrylate, tricyclodecyl methyl (meth)acrylate and / or 2-(p-cumylphenoxy)ethyl methacrylate, relative to the total mass of the material, (b) 33 to 55% by weight, relative to the total mass of the material, of at least one urethane di(meth)acrylate telechelic compound having a number-average molar mass of 750 to 2000 g / mol and at least 4 urethane groups, prepared by reacting 1 mol of ethoxylated or propoxylated bisphenol A, decanediol or dodecanediol with 2 mol of isophorone diisocyanate (IPDI) and then with 2 mol of 2-hydroxyethyl methacrylate (HEMA) or hydroxypropyl methacrylate (HPMA), (d) 2 to 10 wt. % relative to the total mass of the material of at least one ABA or AB block copolymer, wherein the A blocks consist of oligomeric polycaprolactone, poly(2,6-dimethyl-1,4-phenylene oxide), poly(ethylene oxide), poly(propylene oxide) or poly(meth)acrylate structural units and the B blocks consist of poly(dimethylsiloxane), poly(isoprene), poly(vinyl acetate), poly(isobutylene), cis-poly(butadiene) or poly(ethylene) structural units, (e) 0.1 to 5.0 wt. % of at least one photoinitiator and (g) 0.2 to 5% by weight of one or more other additives relative to the total mass of the material, And wherein the dental material is substantially free of di(meth)acrylate monomers and core-shell polymer particles.
14. The free-radically polymerizable dental material according to any one of claims 1 to 4, having a transparency of ≥60% and a viscosity of ≤10.0 Pa∙s at 25°C.
15. A free-radically polymerizable dental material according to any one of claims 1 to 4, which after curing has a molecular weight of 300 to 5000 mol / m 3 cross-linking density.
Citation Information
Patent Citations
improved infill tiled stove
CH31716A
Use of radically hardening compositions in generative production methods
EP3020361A1
Photocurable composition, denture base, and removable denture
EP3494954A1
Curable composition for use in a high temperature photopolymerisation method on a lithography basis and process for the preparation of cross-linked polymers therefrom
EP3564282A1
Three-dimensional fabricating material systems and methods for producing layered dental products
US10299896B2